Use of organic enrichment as additives in coconut coir dust on development of tomato in soilless culture - Mokhtari, Solmaz; Ismail, Mohd Razi; Kausar, Hossain; Musa, Mohamed Hanafi; Megat Wahab, Puteri Edaroyati; Berahim, Zulkarami; Omar, Mohamad Husni; Habib, Sheikh Hasna (Taylor & Francis, 2013)
Amendment of empty fruit bunch (EFB) and vermicompost (VC) in coconut coir dust (CD) has been promoted as a potential alternate media in soilless culture. However, in commercial overview, several problems can be seen in the use of amendment with coconut coir dust as a growth media. The aim of this study was to investigate the effect of EFB and VC as organic amendment (10%–40%; v/v) on the growth and yield of tomato plant in CD media. Six treatments were used with five replications. A 100% CD with nutrient solution (electrical conductivity [EC] = 2.5 mS · cm−1) was used as control treatment. The other treatments were 30 EFB, 10, 20, 30, and 40% VC, which were equivalent to half strength of the nutrients supplied in control. The results showed that plants grown in CD with 20% VC had higher vegetative growth and yield.